Cell therapy for spinal cord injury using induced pluripotent stem cells - Nagoshi, Narihito; Tsuji, Osahiko; Nakamura, Masaya; Okano, Hideyuki (Regenerative therapy, 2019)
For the past few decades, spinal cord injury (SCI) has been believed to be an incurable traumatic condition, but with recent developments in stem cell biology, the field of regenerative medicine has gained hopeful momentum in the development of a treatment for this challenging pathology. Among the treatment candidates, transplantation of neural precursor cells has gained remarkable attention as a reasonable therapeutic intervention to replace the damaged central nervous system cells and promote functional recovery. Here, we highlight transplantation therapy techniques using induced pluripotent stem cells to treat SCI and review the recent research giving consideration to future clinical applications. •Transplantation of iPSC-derived neural precursor cells (NPCs) shows beneficial effects for spinal cord injury (SCI).•Because unsafe iPSC-NPC lines can form tumors after grafting, provisions to attenuate this risk are substantially important.•Clinical application for SCI patients using iPSCs will be conducted in the near future.